Parents, Peers, and Musical Play: Integrated Parent-Child Music Class Program Supports Community Participation and Well-Being for Families of Children With and Without Autism Spectrum Disorder - Lense, Miriam D.; Beck, Sara; Liu, Christina; Pfeiffer, Rita; Diaz, Nicole; Lynch, Megan; Goodman, Nia; Summers, Adam; Fisher, Marisa H. (Frontiers in Psychology, 2020)
Opportunities for meaningful community participation may influence the development and well-being of individuals with autism spectrum disorder (ASD) and their families as well as impact how community members perceive and understand ASD. In the current study, we aimed to understand how a parent-child integrated music class program could be used to promote community participation and family well-being. Caregivers of preschoolers (2-5 years of age) with ASD and those of peer children with typical development were interviewed about their participation in a parent-child integrated music class program. Thematic analysis of interviews revealed that all caregivers viewed program participation as positive. Caregivers emphasized increasing connections within families, such as through strengthening parent-child bonds, as well as connections across families, including increased understanding of ASD and sensitivity to the experience of parenting. Many caregivers perceived the class as supporting their parenting and impacting their children’s behavior in meaningful ways. Interview themes were supported by measures of caregiver and child program receipt, including questionnaires about family music engagement throughout their time in the class program and behavioral coding of children’s engagement during music classes. Findings suggest that integrated community experiences such as parent-child music classes may impact whole family well-being, highlighting the value of integrated community participation experiences at the level of the family system. Parent-child music classes may provide a productive and accessible context for supporting integrated community experiences.